FGF11 induced by hypoxia interacts with HIF-1 alpha and enhances its stability - Lee, Kyeong Won; Yim, Hyung-Soon; Shin, Jihye; Lee, Cheolju; Lee, Jung-Hyun; Jeong, Jae-Yeon (WILEY, 2017)
Fibroblast growth factor 11 (FGF11) is an intracellular FGF. Although induction of FGF11 by hypoxia has been observed in several cell types, the molecular function of FGF11 is not clearly understood yet. Here, we investigated the role of FGF11 under hypoxia. We identified hypoxia-inducible factor-1 alpha (HIF-1 alpha) as an interacting protein of FGF11 using immunoprecipitation and mass spectrometry. FGF11 knockdown decreased HIF-1 alpha protein, while FGF11 overexpression increased it, without affecting HIF-1 alpha mRNA. Protein stability test and ubiquitination assay showed that FGF11 increased HIF-1 alpha stability by acting upstream of proteasomal degradation. Altogether, these results suggest a cross-regulation between HIF-1a and FGF11, through which hypoxia-induced FGF11 reinforces hypoxia responses by enhancing the stability of HIF-1 alpha.
Keywords: FACTOR HOMOLOGOUS FACTORS; INDUCIBLE FACTORS; EXPRESSION; CANCER; CELLS; INDUCTION; EVOLUTION; THERAPY; PROTEIN